Phytoextraction of Cr(VI) from soil using Portulaca oleracea - Alyazouri, Ayman (2014)
Cr(VI) represents an environmental challenge in both soil and water as it is soluble and bioavailable over a wide range of pH. In previous investigations, Portulaca oleracea (a plant local to the United Arab Emirates (UAE)) demonstrated particular ability for the phytoextraction of Cr(VI) from calcareous soil of the UAE. In this publication, the results of the evaluation of P. oleracea phytoextraction of Cr(VI) from UAE soil at higher concentrations are reported. P. oleracea was exposed to nine different concentrations of Cr(VI) in soil from 0 to 400 mg kg−1. The uptake of Cr(VI) increased as its concentration in soil increased between 50 and 400 mg kg−1, with the most efficient removal in the range from 150 to 200 mg kg−1. The total chromium concentrations exceeded 4600 mg kg−1 in roots and 1400 mg kg−1 in stems, confirming the role of P. oleracea as an effective Cr(VI) accumulator. More than 95% of the accumulated Cr(VI) was reduced to the less toxic Cr(III) within the plant.